Resin composition, molded body, and application of the same
Patent Information
- Application Number
- JP2023149574
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
Smart Images

Figure 2025042510000001 
Figure 2025042510000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a molded article, and uses thereof. [Background technology]
[0002] Among thermoplastic resins, polyolefins have been widely used in daily necessities. Polyolefins can be mass-produced by injection molding, have a low specific gravity, excellent mechanical strength, and have various features such as gloss, colorability, chemical resistance, and recyclability. However, thin-walled molded bodies using polyolefins can be easily damaged by impact loads. For example, if a rib structure is provided as the shape of the molded body, the molded body can exhibit a buffering effect against impact loads and prevent damage, but if the shape is such that it is difficult to provide a rib structure, a molding material filled with inorganic fillers can be used to improve impact strength.
[0003] Polyolefins have also been widely used in toys. For the purpose of improving impact resistance, molding materials filled with inorganic fillers are used for thin-walled toys, just like for everyday items. Such molding materials tend to be hard, and because of their hard feel, they are less likely to change shape, so for example, young children who often have the opportunity to handle toys may get bored of playing with them.
[0004] On the other hand, polystyrene-based thermoplastic elastomers are used in daily necessities and toys because of their elasticity similar to that of rubber materials. For example, styrene-ethylene-butylene-styrene copolymer (SEBS) has a structural unit in which a hard polystyrene portion (hard segment) and a soft polybutylene portion (soft segment) are copolymerized in a block shape. It is known that the terminal blocks of polystyrene form a structure (domain) in which they are aggregated with each other, and the domain becomes a pseudo-crosslinking point, and polystyrene exhibits elasticity similar to that of rubber materials. However, polystyrene is also a resin with strong self-adhesiveness (tackiness), and for example, during injection molding, the molded body sticks to the mold, making mass production difficult. To suppress the self-adhesiveness, molding materials are used that are blended with polystyrene, crystalline polyolefin, etc., or filled with inorganic fillers. However, these molding materials cannot maintain flexibility and tend to produce hard molded bodies.
[0005] Patent Document 1 discloses synthetic paper made of a resin composition containing inorganic mineral powder and polyethylene. Furthermore, Patent Documents 2 and 3 disclose sheet molded articles made of resin compositions containing a specific inorganic filler and polyolefin. Patent Document 2 discloses a resin composition containing equal amounts of polypropylene resin and calcium carbonate, and a sheet made of the resin composition. Patent Document 2 also discloses that polyethylene resin can be used instead of polypropylene resin. Patent Document 3 discloses a resin composition containing a crystalline polymer such as a polypropylene resin and a polyethylene resin, and an inorganic fine powder, and a sheet made of the resin composition. Patent Document 3 also specifically discloses a resin composition containing a propylene homopolymer, calcium carbonate, and a small amount of magnesium stearate as an example of such a resin composition. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2001-071378 A [Patent Document 2] JP 2003-026866 A [Patent Document 3] International Publication No. 2018 / 092494 Summary of the Invention [Problem to be solved by the invention]
[0007] The loss tangent is an index used to evaluate the viscoelasticity of materials such as elastomers when they deform. This loss tangent is a value expressed as the ratio (G'' / G') of the loss modulus (G'') to the storage modulus (G'), and is known as tan δ. Materials with a large tan δ tend to have a soft feel when molded into a molded product. Furthermore, materials with a high tan δ at room temperature soften when they come into contact with the skin, making them suitable for use in wearable applications where they come into contact with human skin.
[0008] The resin composition described in Patent Document 1 can be used as synthetic paper and has excellent foldability and tearability, but does not exhibit a high maximum value of tan δ (peak tan δ value) and is a material that is poor in flexibility and compatibility with the skin. It is described that the resin compositions described in Patent Documents 2 and 3 have good moldability despite containing a large amount of inorganic filler, and it is presumed that the stickiness of the surface of the molded product is eliminated. However, since the resin compositions described in Patent Documents 2 and 3 contain a large amount of inorganic filler, the molded product obtained tends to be hard and lose flexibility, so that it is difficult to express a high tan δ peak value in the first place.
[0009] Therefore, an object of the present invention is to provide a resin composition which has excellent moldability, particularly mold releasability, and which is flexible, heavy, and has high skin compatibility, and a molded article thereof. [Means for solving the problem]
[0010] As a result of intensive investigations aimed at solving the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by using a resin composition containing a 4-methyl-1-pentene / α-olefin copolymer (A), an inorganic filler (B), and a specific thermoplastic elastomer (C) in a specific blending ratio, and have thus completed the present invention.
[0011] That is, the present invention relates to, for example, the following items [1] to
[13] .
[0012] [1] 15 to 50 parts by mass of a 4-methyl-1-pentene / α-olefin copolymer (A); 10 to 80 parts by mass of an inorganic filler (B); a thermoplastic elastomer (C) of 5 to 50 parts by mass (wherein the total amount of the 4-methyl-1-pentene / α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C) is 100 parts by mass); A resin composition comprising: The resin composition satisfies the following requirements (Xa) to (Xc), The 4-methyl-1-pentene / α-olefin copolymer (A) satisfies the following requirements (Aa) to (Ab): the thermoplastic elastomer (C) is at least one selected from the group consisting of a polyolefin-based thermoplastic elastomer (C1) and a polystyrene-based thermoplastic elastomer (C2); The polyolefin-based thermoplastic elastomer (C1) satisfies the following requirement (C1-a): Resin composition (X); (Xa) - In the temperature range of 60 to 150°C, the tan δ peak temperature, which is the temperature at which the loss tangent tan δ value obtained by dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) is maximum, is 0°C or higher and 60°C or lower; (Xb) The peak value of tan δ, which is the maximum value of loss tangent tan δ determined by dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) in the temperature range of -60 to 150°C, is 0.6 or more and 5.0 or less; (Xc) Density is 1.0 g / cm 3 More than 5.0g / cm 3 Below is; (Aa) the 4-methyl-1-pentene·α-olefin copolymer (A) contains 55 to 90 mol % of structural units derived from 4-methyl-1-pentene and 10 to 45 mol % of structural units derived from an α-olefin having 2 to 4 carbon atoms (wherein the total of the structural units derived from 4-methyl-1-pentene and the structural units derived from an α-olefin having 2 to 4 carbon atoms is 100 mol %); (Ab) the tan δ peak temperature is 15° C. or more and 45° C. or less; (C1-a) The tan δ peak temperature is less than 15°C.
[0013] [2] The resin composition (X) according to [1], comprising more than 50 parts by mass and not more than 80 parts by mass of the inorganic filler (B).
[0014] [3] The resin composition (X) according to [1] or [2], wherein the 4-methyl-1-pentene / α-olefin copolymer (A) satisfies the following requirements (Ac) to (Ad): (Ac) the tan δ peak value is 0.6 or more and 5.0 or less; (Ad) The melting point as measured by a differential scanning calorimeter (DSC) is 160° C. or lower, or no melting point is observed by a differential scanning calorimeter (DSC).
[0015] [4] The resin composition (X) according to any one of [1] to [3], wherein the inorganic filler (B) is at least one selected from the group consisting of calcium carbonate, magnesium sulfate, barium sulfate, magnesium oxide and talc.
[0016] [5] The resin composition (X) according to any one of [1] to [4], wherein the inorganic filler (B) has an average particle size of 0.01 to 100 μm.
[0017] [6] A molded article made of the resin composition (X) according to any one of [1] to [5].
[0018] [7] A wearable member comprising the resin composition (X) according to any one of [1] to [5].
[0019] [8] A toy comprising the resin composition (X) according to any one of [1] to [5].
[0020] [9] An ear insert member comprising the resin composition (X) according to any one of [1] to [5].
[0021]
[10] A wristwatch component comprising the resin composition (X) according to any one of [1] to [5].
[0022]
[11] A spectacle member comprising the resin composition (X) according to any one of [1] to [5].
[0023]
[12] Stationery comprising the resin composition (X) according to any one of [1] to [5].
[0024]
[13] [1]-[5]. Tableware comprising the resin composition (X) according to any one of the above. Effect of the Invention
[0025] According to the present invention, it is possible to provide a resin composition and a molded article which are excellent in moldability, particularly mold releasability, and which are flexible, heavy, and have high skin compatibility. In particular, the resin composition and molded article of the present invention have excellent flexibility and good compatibility with the skin even when they contain a large amount of inorganic filler. The molded article made of the resin composition of the present invention can provide, for example, daily necessities, toys, stationery, tableware, and wearable components such as earpieces, wristwatch components, and eyeglass components, which have high stress relaxation properties, shape retention that slowly recovers to the original shape after elastic deformation, and flexibility and weight. Therefore, the molded article is suitable for, for example, daily necessities, toys, stationery, tableware, and wearable components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be practiced with appropriate modifications within the scope of the object of the present invention. In this specification, the terms "polymer" and "(co)polymer" are used to include homopolymers and copolymers unless otherwise specified.
[0027] <Resin composition (X)> The resin composition (X) of the present invention contains a 4-methyl-1-pentene·α-olefin copolymer (A), an inorganic filler (B), and a thermoplastic elastomer (C). Specifically, the resin composition (X) contains 15 to 50 parts by mass of a 4-methyl-1-pentene·α-olefin copolymer (A), 10 to 80 parts by mass of an inorganic filler (B), and 5 to 50 parts by mass of a thermoplastic elastomer (C) (wherein the total amount of the 4-methyl-1-pentene·α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C) is 100 parts by mass). The thermoplastic elastomer (C) is at least one selected from the group consisting of a polyolefin-based thermoplastic elastomer (C1) and a polystyrene-based thermoplastic elastomer (C2). The 4-methyl-1-pentene·α-olefin copolymer (A) and the thermoplastic elastomer (C) may be obtained from raw materials derived from biomass.
[0028] The resin composition (X) satisfies all of the following requirements (Xa) to (Xc).
[0029] Requirement (Xa) The requirement (Xa) is that the tan δ peak temperature of the resin composition (X), which is the temperature at which the loss tangent tan δ value obtained by dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) is maximum in the temperature range of -60 to 150°C, is 0°C or higher and 60°C or lower. The tan δ peak temperature of the resin composition (X) is preferably 2°C or higher, more preferably 4°C or higher. The tan δ peak temperature of the resin composition (X) is preferably 55°C or lower, more preferably 50°C or lower, and particularly preferably 45°C or lower. By adjusting the tan δ peak temperature of the resin composition (X) to the above range, a molded article made of the resin composition (X) exhibits high stress relaxation properties over a wide range of environmental temperatures.
[0030] <Requirements (Xb)> Requirement (Xb) is that the resin composition (X) has a tan δ peak value, which is the maximum value of loss tangent tan δ determined by dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) in a temperature range of -60 to 150°C, of 0.6 to 5.0. The tan δ peak value in the resin composition (X) is preferably 0.6 to 4.5, more preferably 0.6 to 4.0, and particularly preferably 0.6 to 3.5. By adjusting the tan δ peak value of the resin composition (X) within the above range, the obtained molded article has excellent stress relaxation properties and can slowly recover to its original shape after elastic deformation.
[0031] The loss tangent tan δ can be calculated from the ratio (G″ / G′) of the storage modulus (G′) to the loss modulus (G″) measured by dynamic viscoelasticity measurement. In the present invention, the loss tangent tanδ is determined by dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) in a temperature range of -60 to 150°C, and the temperature at which the loss tangent tanδ is maximum in this temperature range is defined as the tanδ peak temperature, and the value of the loss tangent tanδ at that time is defined as the tanδ peak value. The tanδ peak temperature in the resin composition (X) is considered to be due to the glass transition temperature of the resin composition (X). Details of the method for measuring the dynamic viscoelasticity are as described in the Examples section below.
[0032] <Requirements (Xc)> The requirement (Xc) is that the density of the resin composition (X) is 1.0 g / cm 3 More than 5.0g / cm 3 The density of the resin composition (X) is 1.05 g / cm or less. 3 It is preferable that the content is 1.1 g / cm or more. 3 More preferably, it is 1.2 g / cm or more. 3 It is more preferable that the density of the resin composition (X) is 4.5 g / cm or more. 3 It is preferable that the density is 4.0 g / cm or less. 3 It is more preferable that: If the density of the resin composition (X) is within the above range, it is preferable because a weighty feeling can be obtained when the resin composition (X) is molded into a molded product. For example, if the resin composition (X) is used for daily necessities or tableware, it is expected to be stable when placed on a desk or table. Details of the method for measuring density are as described in the Examples section below.
[0033] When the resin composition (X) is formed into a sheet-like molded product, the lower limit of the Shore A hardness (measured in accordance with ASTM D2240, with six sheet-like molded products having a thickness of 1.0 mm stacked together) 15 seconds after the start of contact with the indenter with the surface of the molded product is preferably 10, more preferably 20, and even more preferably 40. On the other hand, the upper limit of the Shore A hardness 15 seconds after the start of contact with the indenter is preferably 95, more preferably 92, and even more preferably 88. The method for producing the sheet-like molded product is as shown in the Examples section.
[0034] When the resin composition (X) is molded into a sheet-like molded article, the lower limit of the change ΔHS in Shore A hardness (measured in accordance with ASTM D2240, with six sheet-like molded articles having a thickness of 1.0 mm stacked together) defined by the following formula is preferably 5, more preferably 8, and even more preferably 10. On the other hand, the upper limit of ΔHS is preferably 60, more preferably 50, and even more preferably 40. ΔHS = (Shore A hardness value immediately after the indenter starts contacting the surface - Shore A hardness value 15 seconds after the indenter starts contacting the surface) The ΔHS can be changed arbitrarily by adjusting the contents of the 4-methyl-1-pentene·α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C). When the ΔHS is within the above range, the resin composition (X) has excellent flexibility and compatibility with the skin.
[0035] When it is difficult to measure the Shore A hardness, the same evaluation can be performed using the Shore D hardness instead. In this case, instead of ΔHS, the evaluation can be performed using the change in the Shore D hardness (measured in accordance with ASTM D2240, with six 1.0 mm thick sheet-like molded bodies stacked together) ΔHS' defined by the following formula. ΔHS' = (Shore D hardness value immediately after the indenter starts contacting the specimen - Shore D hardness value 15 seconds after the indenter starts contacting the specimen)
[0036] The lower limit of ΔHS' is preferably 5, more preferably 8, and even more preferably 10. On the other hand, the upper limit of ΔHS' is preferably 60, more preferably 50, and even more preferably 40. Like ΔHS, ΔHS' can be changed arbitrarily by adjusting the contents of the 4-methyl-1-pentene / α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C). When ΔHS' is within the above range, the resin composition (X) has excellent flexibility and compatibility with the skin.
[0037] <4-Methyl-1-pentene / α-olefin copolymer (A)> The 4-methyl-1-pentene·α-olefin copolymer (A) satisfies the following requirements (Aa) to (Ab). The 4-methyl-1-pentene·α-olefin copolymer (A) preferably satisfies one or more of the following requirements (Ac) to (Ai), more preferably two or more of them, and further preferably all of them.
[0038] <Requirement (Aa)> Requirement (Aa) is that the 4-methyl-1-pentene·α-olefin copolymer (A) contains 55 to 90 mol % of structural units derived from 4-methyl-1-pentene (hereinafter may be referred to as "structural units (i)") and 10 to 45 mol % of structural units derived from an α-olefin having 2 to 4 carbon atoms (hereinafter may be referred to as "structural units (ii)") (with the total of structural units (i) and structural units (ii) being 100 mol %).
[0039] A structural unit derived from an α-olefin means a structural unit corresponding to an α-olefin, i.e., a structural unit represented by -CH2-CHR- (R is a hydrogen atom or an alkyl group). Similarly, a structural unit derived from 4-methyl-1-pentene means a structural unit corresponding to 4-methyl-1-pentene (i.e., a structural unit represented by -CH2-CH(-CH2CH(CH3)2)-).
[0040] The content of the structural unit (i) in the 4-methyl-1-pentene / α-olefin copolymer (A) is 55 mol% or more, preferably 60 mol% or more, and more preferably 68 mol% or more, and is 90 mol% or less, preferably 86 mol% or less, and more preferably 84 mol% or less. When the content of structural unit (i) in the 4-methyl-1-pentene / α-olefin copolymer (A) is within the above range, the tan δ peak temperature of the 4-methyl-1-pentene / α-olefin copolymer (A) measured by dynamic viscoelasticity measurement is near room temperature, and therefore the tan δ peak temperature of the resin composition (X) can also be easily adjusted to be within the above range.
[0041] Therefore, in the 4-methyl-1-pentene·α-olefin copolymer (A), the content of the structural unit (ii) is 45 mol % or less, preferably 40 mol % or less, more preferably 32 mol % or less, and is 10 mol % or more, preferably 14 mol % or more, more preferably 16 mol % or more.
[0042] The content (mol%) of each structural unit constituting the 4-methyl-1-pentene / α-olefin copolymer (A) is 13 The content of each structural unit is measured by C-NMR. Details of the method for measuring the content of each structural unit are as described in the Examples section below.
[0043] Examples of the α-olefin having 2 to 4 carbon atoms include ethylene, propylene, and 1-butene, and propylene is preferred. The α-olefin having 2 to 4 carbon atoms from which the structural unit (ii) is derived may be one type or two or more types. When propylene is used as the α-olefin having 2 to 4 carbon atoms, the 4-methyl-1-pentene / α-olefin copolymer (A) has uniform and good kneadability with the inorganic filler (B) and the thermoplastic elastomer (C), and a molded article made of the resin composition (X) has flexibility. In a typical embodiment of the present invention, the 4-methyl-1-pentene·α-olefin copolymer (A) is composed only of the structural unit (i) and the structural unit (ii).
[0044] The 4-methyl-1-pentene / α-olefin copolymer (A) may further contain, in addition to the structural units (i) and (ii), structural units derived from other polymerizable monomers other than 4-methyl-1-pentene and α-olefins having 2 to 4 carbon atoms, so long as the amount is small enough not to impair the object of the present invention, specifically 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less, relative to 100 mol % in total of the structural units (i) and (ii).
[0045] Examples of other polymerizable monomers include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentane, and vinylcyclohexane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; and non-conjugated polyenes, such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, dicyclopentadiene, cyclohexadiene, dicyclooctadiene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, and 5-methylene-2-norbornene. The constitutional units derived from other polymerizable monomers may be of one type or of two or more types.
[0046] <Requirements (Ab)> The requirement (Ab) is that the tan δ peak temperature in the 4-methyl-1-pentene / α-olefin copolymer (A) is 15° C. or more and 45° C. or less. The tan δ peak temperature in the 4-methyl-1-pentene / α-olefin copolymer (A) is preferably 20° C. or more and 45° C. or less, more preferably 25° C. or more and 45° C. or less. By setting the tan δ peak temperature of the 4-methyl-1-pentene·α-olefin copolymer (A) within the above range, the resin composition (X) has excellent stress relaxation properties at around room temperature.
[0047] <Requirements (Ac)> The requirement (Ac) is that the tan δ peak value in the 4-methyl-1-pentene / α-olefin copolymer (A) is usually 0.6 or more and 5.0 or less. The tan δ peak value in the 4-methyl-1-pentene / α-olefin copolymer (A) is preferably 1.0 or more and 5.0 or less, more preferably 1.5 or more and 5.0 or less, and even more preferably 2.0 or more and 4.0 or less. By setting the tan δ peak value of the 4-methyl-1-pentene·α-olefin copolymer (A) within the above range, the resin composition (X) has excellent restoring property in which it tends to gradually return to its original shape depending on the tensile stress or the deformation rate.
[0048] <Requirements (Ad)> The requirement (Ad) is that the 4-methyl-1-pentene·α-olefin copolymer (A) preferably has a melting point of 160° C. or less as measured by a differential scanning calorimeter (DSC), or no melting point is observed by a differential scanning calorimeter (DSC). The 4-methyl-1-pentene·α-olefin copolymer (A) more preferably has a melting point of 140° C. or less as measured by DSC, or no melting point is observed by DSC, and even more preferably no melting point is observed by DSC. The melting point measured by DSC is the highest temperature at the apex of the melting peak measured at a heating rate of 10° C. / min in accordance with JIS K7121. When the 4-methyl-1-pentene / α-olefin copolymer (A) satisfies the requirement (Ad), the 4-methyl-1-pentene / α-olefin copolymer (A) has excellent kneadability with the inorganic filler (B) and the thermoplastic elastomer (C), and the stress relaxation property of the resin composition (X) can be improved.
[0049] <Requirements (Ae)> The requirement (Ae) is that the intrinsic viscosity [η] of the 4-methyl-1-pentene-α-olefin copolymer (A) measured in decalin at 135° C. is preferably in the range of 0.1 to 5.0 dl / g. The intrinsic viscosity [η] of the 4-methyl-1-pentene-α-olefin copolymer (A) is more preferably in the range of 0.5 to 4.0 dl / g, and even more preferably in the range of 1.0 to 3.5 dl / g. As described later, the molecular weight can be controlled by using hydrogen in the polymerization of the 4-methyl-1-pentene-α-olefin copolymer (A), and the intrinsic viscosity [η] of the 4-methyl-1-pentene-α-olefin copolymer (A) can be adjusted to the above range. Details of the method for measuring the intrinsic viscosity [η] are as described in the Examples section below.
[0050] <Requirements (Af)> The requirement (Af) is that the weight average molecular weight (Mw) of the 4-methyl-1-pentene / α-olefin copolymer (A) measured by gel permeation chromatography (GPC) is preferably in the range of 1,000 to 1,000,000 in terms of polystyrene. The Mw of the 4-methyl-1-pentene / α-olefin copolymer (A) is more preferably in the range of 5,000 to 800,000, and even more preferably in the range of 10,000 to 500,000. Details of the method for measuring Mw are as described in the Examples section below.
[0051] <Requirements (Ag)> The requirement (Ag) is that the molecular weight distribution (Mw / Mn), which is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) in the 4-methyl-1-pentene / α-olefin copolymer (A) measured by gel permeation chromatography (GPC), is preferably in the range of 1.0 to 3.5. The Mw / Mn in the 4-methyl-1-pentene / α-olefin copolymer (A) is more preferably in the range of 1.2 to 3.0, and even more preferably in the range of 1.5 to 2.8. When the molecular weight distribution (Mw / Mn) of the 4-methyl-1-pentene / α-olefin copolymer (A) is in the above range, the influence of low molecular weight and low stereoregularity polymers derived from the composition distribution is small, and the mechanical strength of the obtained molded article is less likely to decrease, which is preferable.
[0052] <Requirements (Ah)> The requirement (Ah) is that the melt mass flow rate (MFR; based on ASTM D1238, temperature 230°C, load 2.16 kg) of the 4-methyl-1-pentene / α-olefin copolymer (A) is preferably in the range of 0.1 to 100 g / 10 min. The MFR of the 4-methyl-1-pentene / α-olefin copolymer (A) is more preferably in the range of 0.5 to 50 g / 10 min., and even more preferably in the range of 1.0 to 30 g / 10 min. When the melt mass flow rate (MFR) of the 4-methyl-1-pentene / α-olefin copolymer (A) is at least the lower limit of the above range, the dispersibility of the 4-methyl-1-pentene / α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C) is good. When the MFR is at most the upper limit of the above range, the molecular weight of the 4-methyl-1-pentene / α-olefin copolymer (A) is not too low, and the molded article has sufficient mechanical strength.
[0053] <Requirements (Ai)> The requirement (Ai) is that the density of the 4-methyl-1-pentene / α-olefin copolymer (A) is preferably 830 to 870 kg / m 3 The density of the 4-methyl-1-pentene / α-olefin copolymer (A) is more preferably in the range of 830 to 860 kg / m3 , more preferably 830 to 850 kg / m 3 The details of the method for measuring the density are as described in the Examples section below. The density of the 4-methyl-1-pentene·α-olefin copolymer (A) can be appropriately changed by changing the comonomer composition ratio of the 4-methyl-1-pentene·α-olefin copolymer (A). The 4-methyl-1-pentene·α-olefin copolymer (A) having a density within the above range has excellent mixability with the inorganic filler (B) and has uniform and good dispersibility in the thermoplastic elastomer (C), i.e., in both the polyolefin-based thermoplastic elastomer (C1) and the polystyrene-based thermoplastic elastomer (C2).
[0054] The content of the 4-methyl-1-pentene·α-olefin copolymer (A) in the resin composition (X) is 15 to 50 parts by mass relative to 100 parts by mass of the total amount of the 4-methyl-1-pentene·α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C). The content of the 4-methyl-1-pentene·α-olefin copolymer (A) in the resin composition (X) is preferably a certain amount or more, more preferably 20 parts by mass or more, in order that a molded article made of the resin composition (X) can exhibit a high tan δ peak value. On the other hand, the content is preferably a certain amount or less, more preferably 40 parts by mass or less, in order that a molded article made of the resin composition (X) can have a heavy feel.
[0055] <Production method of 4-methyl-1-pentene / α-olefin copolymer (A)> The 4-methyl-1-pentene / α-olefin copolymer (A) can be produced, for example, by polymerizing 4-methyl-1-pentene, an α-olefin having 2 to 4 carbon atoms, and, if desired, other polymerizable monomers in the presence of a suitable polymerization catalyst such as a magnesium-supported titanium catalyst or a metallocene catalyst.
[0056] As the polymerization catalyst that can be used for polymerization, conventionally known catalysts, such as magnesium-supported titanium catalysts and metallocene catalysts, are preferably used.As the metallocene catalyst, for example, the metallocene catalysts described in WO 01 / 53369, WO 01 / 27124, JP-A-3-193796, JP-A-2-41303, WO 2011 / 055803, and WO 2014 / 050817 are preferably used.Polymerization can be carried out by appropriately selecting from liquid phase polymerization methods including solution polymerization and suspension polymerization, and gas phase polymerization methods.
[0057] In the liquid phase polymerization method, an inert hydrocarbon solvent can be used as the solvent constituting the liquid phase. Examples of inert hydrocarbons include aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, halogenated hydrocarbons, and mixtures thereof. Examples of aliphatic hydrocarbons include propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene. Examples of alicyclic hydrocarbons include cyclopentane, cyclohexane, methylcyclopentane, and methylcyclohexane. Examples of aromatic hydrocarbons include benzene, toluene, and xylene. Examples of halogenated hydrocarbons include ethylene chloride, chlorobenzene, dichloromethane, trichloromethane, and tetrachloromethane.
[0058] In addition, in the liquid phase polymerization method, bulk polymerization can also be performed using a monomer corresponding to the structural unit (i) (i.e., 4-methyl-1-pentene) or a monomer corresponding to the structural unit (ii) (i.e., an α-olefin having 2 to 4 carbon atoms) itself as a solvent. Furthermore, by carrying out copolymerization of 4-methyl-1-pentene with an α-olefin having 2 to 4 carbon atoms in stages, it is also possible to appropriately control the composition distribution of the structural units (i) and (ii).
[0059] The polymerization temperature is preferably −50 to 200° C., more preferably 0 to 100° C., and further preferably 20 to 100° C. The polymerization pressure is preferably normal pressure to 10 MPa gauge pressure, and more preferably normal pressure to 5 MPa gauge pressure.
[0060] During polymerization, hydrogen may be added for the purpose of controlling the molecular weight and polymerization activity of the polymer produced. The amount of hydrogen added is appropriately about 0.001 to 100 NL when the total amount of 4-methyl-1-pentene and the amount of α-olefin having 2 to 4 carbon atoms is 1 kg.
[0061] <Inorganic filler (B)> The resin composition (X) contains an inorganic filler (B). The inorganic filler (B) plays a role in imparting sufficient weight to the resin composition (X) and further imparting good moldability. The inorganic filler (B) is not particularly limited as long as it is an inorganic compound, and known fillers can be used. Examples of the inorganic filler (B) include carbon black, graphite, and carbon black surface-treated with a silane coupling agent, finely powdered silicic acid, silica (including fumed silica, precipitated silica, diatomaceous earth, and quartz), oxide fillers including alumina, iron oxide, ferrite, magnesium oxide, titanium oxide, antimony trioxide, zirconium oxide, barium oxide, and calcium oxide, hydroxide fillers including aluminum hydroxide and magnesium hydroxide, silicate fillers including aluminum silicate (clay), magnesium silicate (talc), mica, kaolin, calcium silicate, glass fiber, glass flakes, and glass beads, sedimentary rock fillers including diatomaceous earth and limestone, montmorillonite, magnesian montmorillonite, and the like. Examples of the filler include clay mineral-based fillers including ferrite, ferromontmorillonite, ferromagnesianmontmorillonite, beidellite, aluminianbeidellite, nontronite, aluminiannontronite, saponite, aluminiansaponite, hectorite, sauconite, stevensite, and bentonite; magnetic fillers including ferrite, iron, and cobalt; conductive fillers including silver, gold, copper, and alloys thereof; thermally conductive fillers including aluminum nitride, boron nitride, and silicon carbide; sulfate-based fillers including aluminum sulfate, magnesium sulfate, barium sulfate, and calcium sulfate; sulfite-based fillers including calcium sulfite; calcium carbonate, basic magnesium carbonate, dolomite, barium titanate, and potassium titanate.
[0062] As the inorganic filler (B), silica, magnesium sulfate, barium sulfate, calcium carbonate, magnesium hydroxide, magnesium oxide, and talc are preferred, magnesium sulfate, barium sulfate, calcium carbonate, magnesium oxide, and talc are more preferred, magnesium sulfate, barium sulfate, calcium carbonate, and talc are further preferred, and from the viewpoints of performance, ease of handling, supply stability, price, and the like, barium sulfate, calcium carbonate, and talc are most preferred. The inorganic filler (B) may be used alone or in combination of two or more kinds.
[0063] The average particle size of the inorganic filler (B) is preferably 0.01 μm to 100 μm, more preferably 0.01 μm to 80 μm, and even more preferably 0.01 μm to 50 μm, from the viewpoint of molding processability of the 4-methyl-1-pentene / α-olefin copolymer (A) and the thermoplastic elastomer (C). The average particle size of the inorganic filler (B) is the 50% average particle size (d50) obtained from a cumulative % distribution curve measured by a laser diffraction particle size distribution measuring device, which is a known method.
[0064] The content of the inorganic filler (B) in the resin composition (X) is 10 to 80 parts by mass relative to 100 parts by mass of the total amount of the 4-methyl-1-pentene-α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C). The content of the inorganic filler (B) in the resin composition (X) is preferably a certain amount or more, more preferably higher than 50 parts by mass, and even more preferably 55 parts by mass or more, from the viewpoint of the mold releasability of the resin composition (X) and the weight and sufficient impact strength of the molded article made of the resin composition (X). On the other hand, from the viewpoint of the high stress relaxation property of the molded article made of the resin composition (X), that is, the shape retention meaning that the molded article slowly recovers to its original shape after elastic deformation, the content is preferably a certain amount or less, more preferably 75 parts by mass or less. When two or more types of inorganic filler (B) are used, the above-mentioned numerical ranges are applied to the total content of the inorganic fillers (B).
[0065] <Thermoplastic elastomer (C)> The resin composition (X) contains a thermoplastic elastomer (C). The thermoplastic elastomer (C) is at least one selected from the group consisting of a polyolefin-based thermoplastic elastomer (C1) and a polystyrene-based thermoplastic elastomer (C2). The polyolefin-based thermoplastic elastomer (C1) and the polystyrene-based thermoplastic elastomer (C2) each play a role in adjusting the tan δ peak temperature in the resin composition (X) to a range of 0°C or more and 60°C or less.
[0066] <Polyolefin-based thermoplastic elastomer (C1)> The polyolefin-based thermoplastic elastomer (C1) is not particularly limited as long as it satisfies the requirement (C1-a), and any conventionally known resin can be used. <Requirement (C1-a)> The requirement (C1-a) is that the tan δ peak temperature in the polyolefin-based thermoplastic elastomer (C1) is less than 15° C. The tan δ peak temperature in the polyolefin-based thermoplastic elastomer (C1) is preferably −60° C. or more and 10° C. or less, more preferably −55° C. or more and 0° C. or less.
[0067] Examples of the polyolefin-based thermoplastic elastomer (C1) include ethylene-based polymers, propylene-based polymers, and butene-based polymers. More specifically, ethylene-based elastomers consisting of ethylene-based copolymers such as copolymers of ethylene and an α-olefin having 3 to 20 carbon atoms, copolymers of ethylene and an α-olefin having 3 to 20 carbon atoms and a cyclic olefin, and ethylene-based copolymers having a vinyl compound as a comonomer, as well as ethylene-based elastomers having an island-sea structure containing polyethylene as a hard segment; Propylene-based elastomers made of propylene-based copolymers such as copolymers of propylene and an α-olefin having 4 to 20 carbon atoms, copolymers of propylene, ethylene and an α-olefin having 4 to 20 carbon atoms, and copolymers of propylene, an α-olefin having 4 to 20 carbon atoms and a cyclic olefin, as well as propylene-based elastomers having an island-sea structure containing polypropylene as a hard segment; and butene-based elastomers consisting of 1-butene copolymers such as copolymers of 1-butene and an α-olefin having 5 to 20 carbon atoms, and copolymers of 1-butene and an α-olefin having 5 to 20 carbon atoms and a cyclic olefin, as well as butene-based elastomers having an island-sea structure containing polybutene as a hard segment; Examples include: Examples of vinyl compounds used in ethylene copolymers include styrene, vinyl acetate, (meth)acrylic acid, and (meth)acrylic acid esters.
[0068] The term "ethylene-based copolymer" refers to a copolymer having ethylene as the main component (specifically, containing 50% by mass or more, preferably 70% by mass or more of structural units derived from ethylene), the term "propylene-based copolymer" refers to a copolymer having propylene as the main component (specifically, containing 50% by mass or more, preferably 70% by mass or more of structural units derived from propylene), and the term "1-butene-based copolymer" refers to a copolymer having 1-butene as the main component (specifically, containing 50% by mass or more, preferably 70% by mass or more of structural units derived from 1-butene).
[0069] In one preferred embodiment of the present invention, the polyolefin-based thermoplastic elastomer (C1) is a copolymer of propylene, ethylene, and an α-olefin having 4 to 20 carbon atoms, and a preferred example of such a copolymer is a copolymer of propylene, ethylene, and 1-butene. The polyolefin-based thermoplastic elastomer (C1) preferably does not contain any structural units derived from 4-methyl-1-pentene. The polyolefin-based thermoplastic elastomer (C1) preferably does not contain any structural units derived from a non-conjugated polyene. The polyolefin-based thermoplastic elastomer (C1) may be of one type alone or of two or more types.
[0070] The polyolefin-based thermoplastic elastomer (C1) may be an unmodified polyolefin-based thermoplastic elastomer, or a modified polyolefin-based thermoplastic elastomer obtained by modifying an unmodified polyolefin-based thermoplastic elastomer with a polar group-containing monomer containing at least one functional group selected from the group consisting of an acid anhydride group, a carboxyl group, an amino group, an imino group, an alkoxysilyl group, a silanol group, a silyl ether group, a hydroxyl group, and an epoxy group. As one of the preferred embodiments of the present invention, the polyolefin-based thermoplastic elastomer (C1) is an unmodified polyolefin-based thermoplastic elastomer.
[0071] As the polyolefin-based thermoplastic elastomer (C1), a propylene-based elastomer consisting of a propylene-based copolymer is preferred from the viewpoints of the kneadability of the 4-methyl-1-pentene / α-olefin copolymer (A) with the inorganic filler (B), the moldability of the resin composition (X), and the flexibility of a molded product consisting of the resin composition (X).
[0072] <Polystyrene-based thermoplastic elastomer (C2)> The polystyrene-based thermoplastic elastomer (C2) is, for example, a block copolymer of a polystyrene block that is the hard part (or crystalline part) and a diene monomer block that is the soft part (or amorphous part), and the hard part may be at both ends of the soft part. Examples of the polystyrene-based thermoplastic elastomer (C2) include styrene-butadiene-styrene copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (HSBR), styrene-ethylene-propylene block copolymer (SEP), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-ethylene-butene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), styrene-isobutylene-styrene copolymer (SIBS), styrene-isobutylene copolymer (SIB), and styrene-ethylene-butene-styrene-styrene copolymer (SEBSS).
[0073] The polystyrene-based thermoplastic elastomer (C2) may be of one type alone or of two or more types. As the polystyrene-based thermoplastic elastomer (C2), commercially available products can also be used.
[0074] An example of HSBR is Dynaron (registered trademark) manufactured by JSR Corporation. Examples of SIS include JSR SIS (registered trademark) manufactured by JSR Corporation, Hybler (registered trademark) manufactured by Kuraray Co., Ltd., and Kraton D (registered trademark) manufactured by Kraton Polymer Japan Co., Ltd. Examples of SEPS include hydrogenated SIS, such as Septon (registered trademark) manufactured by Kuraray Co., Ltd. and Kraton (registered trademark) manufactured by Kraton Polymer Japan Co., Ltd. Examples of SEBS include Tuftec H Series (registered trademark) manufactured by Asahi Kasei Corporation and Kraton (registered trademark) manufactured by Kraton Japan Polymer Co., Ltd. An example of SEBSS is SOE (registered trademark) manufactured by Asahi Kasei Corporation, which has a structure containing styrene even in the soft part. An example of SIB and SIBS is SIBSTAR (registered trademark) manufactured by Kaneka Corporation. Examples of commercially available compounds obtained by combining polystyrene-based thermoplastic elastomers with other resins such as polyolefins include TEFABLOC (registered trademark) manufactured by Mitsubishi Chemical Corporation, ARNESTON (registered trademark) manufactured by Kuraray Plastics Co., Ltd., and ELASTOMER AR Series (registered trademark) manufactured by Aronkasei Co., Ltd.
[0075] <Thermoplastic elastomer (C) content> The content of the thermoplastic elastomer (C) in the resin composition (X) is 5 to 50 parts by mass relative to 100 parts by mass of the total amount of the 4-methyl-1-pentene-α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C). The content of the thermoplastic elastomer (C) in the resin composition (X) is preferably a certain amount or more from the viewpoint of adjusting the tan δ peak temperature of the resin composition (X) to a range of 0°C to 60°C. On the other hand, from the viewpoint of shape retention, which means that a molded article made of the resin composition (X) slowly recovers to its original shape after elastic deformation, the content is preferably a certain amount or less, more preferably 40 parts by mass or less.
[0076] When the thermoplastic elastomer (C) is of two or more types, the above-mentioned numerical ranges are applied to the total content of the thermoplastic elastomers (C) that can be contained in the resin composition (X).
[0077] <Other ingredients> The resin composition (X) contains 4-methyl-1-pentene / α-olefin copolymer (A), inorganic filler (B), and thermoplastic elastomer (C). Here, the resin composition (X) may consist of only 4-methyl-1-pentene / α-olefin copolymer (A), inorganic filler (B), and thermoplastic elastomer (C), or may further contain a component (hereinafter also referred to as "other component") that does not fall under 4-methyl-1-pentene / α-olefin copolymer (A), inorganic filler (B), or thermoplastic elastomer (C) as necessary within a range that does not impair the characteristics of the present invention. Examples of such "other components" include known additives.
[0078] Examples of additives include, but are not limited to, softeners, release agents, antioxidants, flame retardants, ultraviolet absorbers, surfactants, antistatic agents, pigments, dyes, slip agents, weather stabilizers, heat stabilizers, infrared absorbers, antiblocking agents, antifogging agents, lubricants, plasticizers, antioxidants, hydrochloric acid absorbers, crystal nucleating agents, antifungal agents, antibacterial agents, and organic fillers. These additives may be used alone or in combination of two or more.
[0079] Examples of the softening agent include process oil, lubricating oil, petroleum-based substances including paraffin, liquid paraffin, polyethylene wax, polypropylene wax, petroleum asphalt, and vaseline; coal tars including coal tar and coal tar pitch; fatty oils including castor oil, linseed oil, rapeseed oil, soybean oil, tall oil, and coconut oil; waxes including beeswax, carnauba wax, and lanolin; fatty acids or metal salts thereof including ricinoleic acid, palmitic acid, stearic acid, 12-hydroxystearic acid, montanic acid, oleic acid, and erucic acid; synthetic polymers including petroleum resins, coumarone-indene resins, and atactic polypropylene. Examples of the softening agent include known softeners including ester-based plasticizers such as aromatic carboxylates (dioctyl phthalate, dibutyl phthalate, and the like), aliphatic carboxylates (methyl acetyl ricinoleate, and the like), aliphatic dicarboxylates (dioctyl sebacate, dioctyl adipate, adipate-propylene glycol polyesters, and the like), aliphatic tricarboxylates (triethyl citrate, and the like), phosphate triesters (triphenyl phosphate, and the like), and epoxy fatty acid esters (epoxybutyl stearate, and the like), microcrystalline wax, liquid polybutadiene or modified or hydrogenated products thereof, and liquid thiokol.
[0080] Examples of release agents include lower alcohol esters (having 1 to 4 carbon atoms) of higher fatty acids (such as butyl stearate), polyhydric alcohol esters (having 4 to 30 carbon atoms) of fatty acids (such as hydrogenated castor oil), glycol esters of fatty acids, and liquid paraffin.
[0081] Examples of antioxidants include phenolic antioxidants (such as 2,6-di-t-butyl-4-methylphenol), polycyclic phenolic antioxidants (such as 2,2'-methylenebis(4-methyl-6-t-butylphenol) and other methylene-bridged polycyclic phenols), phosphorus antioxidants (such as tetrakis(2,4-di-t-butylphenyl)-4,4-biphenylene diphosphonate), and amine antioxidants (such as N,N-diisopropyl-p-phenylenediamine).
[0082] Examples of the flame retardant include phosphate esters and other phosphorus compounds such as ammonium polyphosphate, ethylene bis tris (2-cyanoethyl) phosphonium chloride, tris (tribromophenyl) phosphate, and tris (3-hydroxypropyl) phosphine oxide; chlorine-based flame retardants such as chlorinated paraffin, chlorinated polyolefin, and perchlorocyclopentadecane; bromine-based flame retardants such as hexabromobenzene, ethylene bis dibromonorbornane dicarboximide, ethylene bis tetrabromophthalimide, tetrabromobisphenol A derivatives, tetrabromobisphenol S, and tetrabromodipentaerythritol; and mixtures thereof.
[0083] Examples of ultraviolet absorbing agents include benzotriazole-based, benzophenone-based, salicylic acid-based, and acrylate-based agents. Examples of antibacterial agents include quaternary ammonium salts, pyridine compounds, organic acids, organic acid esters, halogenated phenols, and organic iodines.
[0084] The surfactants include, for example, nonionic, anionic, cationic and amphoteric surfactants. Examples of nonionic surfactants include polyethylene glycol-type nonionic surfactants such as higher alcohol ethylene oxide adducts, fatty acid ethylene oxide adducts, higher alkylamine ethylene oxide adducts, and polypropylene glycol ethylene oxide adducts, as well as polyhydric alcohol-type nonionic surfactants such as polyethylene oxide, fatty acid esters of glycerin, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol or sorbitan, alkyl ethers of polyhydric alcohols, and fatty amides of alkanolamines. Examples of the anionic surfactant include sulfate salts such as alkali metal salts of higher fatty acids, sulfonates such as alkylbenzenesulfonates, alkylsulfonates, and paraffin sulfonates, and phosphate salts such as higher alcohol phosphate salts. Examples of cationic surfactants include quaternary ammonium salts such as alkyltrimethylammonium salts. Examples of amphoteric surfactants include amino acid type amphoteric surfactants such as higher alkylaminopropionate salts, and betaine type amphoteric surfactants such as higher alkyldimethylbetaines and higher alkyldihydroxyethylbetaines.
[0085] Examples of the antistatic agent include the above-mentioned surfactants, fatty acid esters, and polymeric antistatic agents. Examples of the fatty acid esters include esters of stearic acid and oleic acid, and examples of the polymeric antistatic agents include polyether ester amides.
[0086] Examples of pigments include inorganic pigments (titanium oxide, iron oxide, chromium oxide, cadmium sulfide, etc.) and organic pigments (azo lake-based, thioindigo-based, phthalocyanine-based, and anthraquinone-based). Dyes include, for example, azo-, anthraquinone-, and triphenylmethane-based dyes.
[0087] Examples of slip agents include waxes (such as carnauba wax), higher fatty acids (such as stearic acid), higher fatty acid salts (such as calcium stearate), higher alcohols (such as stearyl alcohol), and higher fatty acid amides (such as stearamide and erucamide).
[0088] The contents of other components such as various additives in the resin composition (X) are preferably 0.01 to 30 parts by mass per 100 parts by mass of the total amount of the 4-methyl-1-pentene / α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C) depending on the application, within a range that does not impair the object of the present invention. The total content of the pigment and dye in the resin composition (X) is not particularly limited, but is usually 5 parts by mass or less, and preferably 0.1 to 3 parts by mass, per 100 parts by mass of the total amount of the 4-methyl-1-pentene / α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C).
[0089] Typical and exemplary embodiments of the resin composition (X) include the following (X1) to (X6): (X1) a resin composition (X) comprising a 4-methyl-1-pentene / α-olefin copolymer (A), an inorganic filler (B), and a polyolefin-based thermoplastic elastomer (C1); (X2) a resin composition (X) comprising a 4-methyl-1-pentene / α-olefin copolymer (A), an inorganic filler (B), and a polystyrene-based thermoplastic elastomer (C2); (X3) a resin composition (X) comprising a 4-methyl-1-pentene / α-olefin copolymer (A), an inorganic filler (B), a polyolefin-based thermoplastic elastomer (C1), and a polystyrene-based thermoplastic elastomer (C2); (X4) A resin composition (X) consisting of only a 4-methyl-1-pentene / α-olefin copolymer (A), an inorganic filler (B), a polyolefin-based thermoplastic elastomer (C1), and various additives; (X5) a resin composition (X) consisting only of a 4-methyl-1-pentene / α-olefin copolymer (A), an inorganic filler (B), a polystyrene-based thermoplastic elastomer (C2), and various additives; (X6) A resin composition (X) consisting only of a 4-methyl-1-pentene·α-olefin copolymer (A), an inorganic filler (B), a polyolefin-based thermoplastic elastomer (C1), a polystyrene-based thermoplastic elastomer (C2), and various additives.
[0090] <Method for producing resin composition (X)> The method for producing the resin composition (X) is not particularly limited, and may be, for example, a conventionally known method, such as a method of dry-blending the 4-methyl-1-pentene-α-olefin copolymer (A), the inorganic filler (B), the thermoplastic elastomer (C), and any "other components" using a known mixer, such as a Henschel mixer, a tumbler blender, or a V-blender.
[0091] As a method for producing the resin composition (X), for example, a method of dry-blending 4-methyl-1-pentene-α-olefin copolymer (A), inorganic filler (B), thermoplastic elastomer (C), and any "other components" in a mixer, melt-kneading the mixture with a single-screw extruder, a twin-screw extruder, a Banbury mixer, a kneader, a roll mill, or the like at a temperature setting of 180 to 250°C, and then granulating or pulverizing the mixture may be adopted. As a method for melt-kneading, melt-kneading with a twin-screw extruder or a Banbury mixer is preferred from the viewpoint of the mixability of each component and productivity. In addition, when melt-kneading with a twin-screw extruder, a method of dry-blending the components other than the inorganic filler (B) and feeding them from a hopper, and feeding the inorganic filler (B) from a side feeder and kneading the components may be used. By these methods, high-quality pellets in which each component is uniformly mixed and dispersed can be obtained.
[0092] The inorganic filler (B) may be used in the form of a mixture with a resin component such as the 4-methyl-1-pentene / α-olefin copolymer (A) or the thermoplastic elastomer (C), for example, in the form of a master batch in which the inorganic filler (B) and a resin component such as the 4-methyl-1-pentene / α-olefin copolymer (A) are premixed.
[0093] <Method of manufacturing molded body> The molded article of the present invention is made of the resin composition (X) of the present invention. Examples of the molded article include wearable members, toys, daily necessities, earpiece members, eyeglass members, wristwatch members, tableware, and stationery, as well as sheet-shaped molded articles. The method for producing the molded body is not particularly limited, and a conventionally known method can be used, for example, injection molding, extrusion sheet molding, and compression molding. The method for producing the molded body is preferably injection molding using a required mold, and the molded body can be suitably produced by such injection molding.
[0094] In addition, when obtaining a sheet-shaped molded product, extrusion sheet molding equipped with a general T-die is preferred. A single-screw extruder or twin-screw extruder equipped with a T-die can be used to form a film at a cylinder temperature of usually 180 to 250°C and a casting roll temperature of usually 20 to 80°C to produce a sheet. The thickness of the sheet is usually 10 to 1000 μm, preferably 20 to 500 μm, depending on the application. When the thickness of the sheet is within the above range, no pinholes are generated during molding, sufficient mechanical strength is obtained, and the sheet is excellent in mass productivity.
[0095] The surface of the sheet may be embossed, and the sheet may be stretched during or after molding. Furthermore, in order to remove residual stress in the sheet, annealing may be performed at a temperature below the melting point of the resin such as 4-methyl-1-pentene / α-olefin copolymer (A).
[0096] <Applications of molded products> The molded article has a high stress relaxation property in the room temperature region, and is characterized by slowly recovering to its original shape after elastic deformation. The molded article is useful not only for daily necessities, wearable parts, toys, ear inserts, eyeglasses, wristwatches, stationery, and seats, but also for conventionally known automobile materials, clothing materials, sanitary materials, construction materials, sports materials, living materials, leisure materials, and industrial materials.
[0097] The molded articles can also be used in the field of household goods, and examples of the uses include containers for holding food, and tableware such as forks, spoons, and plates, etc. These can be easily molded by injection molding, and are useful as containers and tableware to replace ceramics in terms of their weightiness.
[0098] The molded body can be used for other applications using ceramics, such as daily necessities such as lampshades and vases, structural components of certain acoustic speakers, and water-related products such as washbasins and toilets. The molded body can be used for applications other than ceramics, such as models such as plastic models, components for musical instruments, tiles, substitutes for artificial marble, and building components, by utilizing its characteristic of being able to impart a sense of weight. The molded body is also useful as a container for a lid (including airless containers, etc.) and a cosmetic compact. In addition, the molded body is also useful as a filament material for 3D printers by utilizing its moldability and shape retention.
[0099] The molded article can also be used as a wearable member. A wearable member refers to a member that fits closely to the body, and examples of the wearable member include hats and headbands that fit closely to the head, glasses that fit closely to the face, head-mounted display members, earpieces that fit closely to the ears, headphones, mask strings, mouthpieces that come into contact with the mouth, pacifiers, neck wearable members that fit closely to the neck, wristwatch bands and bracelets that fit closely to the arm, underwear, and brassieres that fit closely to the upper and lower body, insoles that fit closely to the feet, and socks. In addition to these, cushions, bedding, and pillows, which are expected to fit closely to the body, are also included in the wearable member.
[0100] Since the resin composition (X) has a high tan δ and a large ΔHS at room temperature, the molded article has good compatibility with the contact part of the body. Furthermore, since the resin composition (X) has excellent mold releasability in injection molding, various parts can be easily molded by applying such molding methods. The molded article can also be suitably used for toys. The resin composition (X) has the property of softening at body temperature, so that the texture of the molded article changes when touched with the hand, making it possible to provide a toy that does not tire of the user. The molded article can be easily deformed by softening with body temperature, but can also retain its shape by cooling after deformation, making it applicable to shape-memory toys. EXAMPLES
[0101] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. Synthesis and characterization of copolymers [Synthesis of 4-methyl-1-pentene-α-olefin copolymer (A-1)]
[0102] [Production Example 1] A 1.5 L stainless steel autoclave equipped with an agitator and thoroughly purged with nitrogen was charged with 300 mL of n-hexane (dried over activated alumina under a dry nitrogen atmosphere) and 450 mL of 4-methyl-1-pentene at 23° C. 0.75 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) was charged into the autoclave and stirred.
[0103] Next, the autoclave was heated to an internal temperature of 60° C., and pressurized with propylene to a total pressure (gauge pressure) of 0.40 MPa. Next, 0.34 mL of a toluene solution containing 1 mmol of methylaluminoxane (calculated as aluminum) and 0.01 mmol of diphenylmethylene(1-ethyl-3-t-butyl-cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, which had been previously prepared, was pressurized into the autoclave with nitrogen to initiate the polymerization reaction.
[0104] During the polymerization reaction, the internal temperature of the autoclave was adjusted to 60°C. 60 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization reaction, and the autoclave was then depressurized to atmospheric pressure. After depressurization, acetone was added to the reaction solution while stirring.
[0105] The obtained powdery copolymer containing the solvent was dried at 100°C under reduced pressure for 12 hours. The product, 4-methyl-1-pentene·α-olefin copolymer (A-1), weighed 36.9 g.
[0106] [Physical properties of copolymers] <Content of structural units> The content of the structural units derived from 4-methyl-1-pentene and the content of the structural units derived from α-olefins in the 4-methyl-1-pentene-α-olefin copolymer (A-1) (hereinafter also referred to as the 4-methyl-1-pentene content and the α-olefin content) were measured using the following apparatus and conditions. 13 The α-olefin content was quantified based on the results of C-NMR measurement. However, the α-olefin content in this measurement does not include the 4-methyl-1-pentene content. The ECP500 nuclear magnetic resonance spectrometer manufactured by JEOL Ltd. was used, and the mixture solvent of orthodichlorobenzene / deuterated benzene (80 / 20% by volume) was used. The sample concentration was 55 mg / 0.6 mL. The measurement temperature was 120°C. The observed nuclei were 13 C (125 MHz), sequence was single pulse proton decoupling, pulse width was 4.7 μs (45° pulse), repetition time was 5.5 s, number of integrations was more than 10,000, and 27.50 ppm was used as the reference value for chemical shift. 13The C-NMR spectrum was measured. 13 The composition of 4-methyl-1-pentene·α-olefin copolymer (A-1) was quantified by C-NMR spectroscopy.
[0107] <Intrinsic viscosity> The intrinsic viscosity [η] was measured in decalin at 135°C using an Ubbelohde viscometer. Approximately 20 mg of the polymer powder, pellets, or resin mass was taken and dissolved in 15 mL of decalin to obtain a decalin solution, and the specific viscosity η was measured in an oil bath heated to 135°C. sp The decalin solution was diluted with 5 mL of decalin solvent, and the specific viscosity η was measured in the same manner. sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity [η] (see the formula below). [η]=lim(η sp / C) (C→0)
[0108] <Weight average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn)> The molecular weight was measured by gel permeation chromatography (GPC). The GPC measurement conditions were as follows: ALC / GPC150-Cplus type (integrated differential refractometer detector) manufactured by Waters was used as a liquid chromatograph, two GMH6-HT manufactured by Tosoh Corporation and two GMH6-HTL were used in series as separation columns, o-dichlorobenzene was used as a mobile phase medium, and 0.025% by mass dibutylhydroxytoluene (manufactured by Takeda Pharmaceutical Co., Ltd.) was used as an antioxidant, the mobile phase medium was moved at 1.0 mL / min, the sample concentration was 15 mg / 10 mL, the sample injection amount was 500 μL, and a differential refractometer was used as a detector. Standard polystyrene manufactured by Tosoh Corporation was used in the range of weight average molecular weight (Mw) of 1,000 or more and 4,000,000 or less. The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) were calculated by preparing a calibration curve using a standard polystyrene sample and analyzing the obtained chromatogram by a known method. The measurement time per sample was 60 minutes.
[0109] <Melt Mass Flow Rate (MFR)> The measurements were performed at a temperature of 230°C and a load of 2.16 kg in accordance with ASTM D1238.
[0110] <Melting point> The melting point was determined as the highest temperature at the apex of the melting peak measured at a heating rate of 10° C. / min using a differential scanning calorimeter DSC220C manufactured by Seiko Instruments Inc. in accordance with JIS K7121.
[0111] <density> The measurement was carried out using a density gradient tube in accordance with JIS K7112.
[0112] <Dynamic viscoelasticity measurement> A predetermined amount of 4-methyl-1-pentene·α-olefin copolymer (A-1) obtained by the above-mentioned method was filled into a SUS mold, and the mixture was preheated for 7 minutes and pressed at a gauge pressure of 10 MPa for 2 minutes using a hydraulic heat press (Kansai Roll Co., Ltd., PEWR-30) with the heating plate set at 200°C. The mixture was then transferred to a cooling plate set at 20°C, compressed at a gauge pressure of 10 MPa, and cooled for 3 minutes to prepare a 1.0 mm thick press sheet for measurement.
[0113] Next, test pieces with dimensions of 35 mm length x 10 mm width were punched out from the 1.0 mm thick measurement press sheet obtained by the above-mentioned method, and the temperature dispersion of the dynamic viscoelasticity was observed from -60 to 150°C using a rheometer (Anton Paar MCR301) under conditions of torsion mode, frequency of 10 rad / s (1.6 Hz), strain setting of 0.1%, and heating rate of 2°C / min. The tan δ peak value was 2.70 and the tan δ peak temperature was 30°C. The measurement results of each physical property are shown in Table 1.
[0114] [Table 1]
[0115] Production and evaluation of resin composition (X) and molded article The following components were used as raw materials for the resin composition (X). [4-Methyl-1-pentene / α-olefin copolymer (A)] As the 4-methyl-1-pentene·α-olefin copolymer (A), the 4-methyl-1-pentene·α-olefin copolymer (A-1) produced in Production Example 1 was used.
[0116] [Inorganic filler (B)] As the inorganic filler (B), inorganic filler (B-1): heavy calcium carbonate (KS-500 manufactured by Calfine Co., Ltd., 50% average particle size 17.7 μm) was used.
[0117] [Polyolefin-based thermoplastic elastomer (C1)] As the polyolefin-based thermoplastic elastomer (C1), polyolefin-based thermoplastic elastomer (C1-1): Toughmer PN-3560 manufactured by Mitsui Chemicals, Inc. (MFR (based on ASTM D1238, temperature 230°C, load 2.16 kg) 6 g / 10 min, density 866 kg / m 3 , melting point 160°C, surface hardness (in accordance with ASTM D2240) Shore A72, tan δ peak temperature -16°C) were used.
[0118] [Polystyrene-based thermoplastic elastomer (C2)] As the polystyrene-based thermoplastic elastomer (C2), polystyrene-based thermoplastic elastomer (C2-1): Kuraray Plastics Co., Ltd.'s Arneston CJ001N (MFR (ASTM D1238 compliant, temperature 230°C, load 2.16 kgf) 2g / 10min, density 0.90g / cm 3 , surface hardness (Shore A40 in accordance with ASTM D2240) was used.
[0119] [Propylene-based resin (D)] As the propylene-based resin (D), propylene-based resin (D-1): Prime Polypro F113G manufactured by Prime Polymer Co., Ltd., which is a propylene homopolymer (MFR (based on ASTM D1238, temperature 230°C, load 2.16 kg) 3g / 10 minutes, melting point 160°C) was used.
[0120] Example 1 [Preparation of resin composition (X-1)] A resin composition (X-1) was produced using a Banbury mixer (Kobe Steel, Ltd. BB-L1800: tangential 4-blade rotor, kneading tank volume 1.63 L) equipped with a single-screw extruder for pelletization. A mixture of 28 parts by mass of 4-methyl-1-pentene-α-olefin copolymer (A-1) and 5 parts by mass of polystyrene-based thermoplastic elastomer (C2-1) that had been dry-blended in advance was charged into the hopper of the Banbury mixer and pushed into the mixing chamber by a floating weight, and 67 parts by mass of inorganic filler (B-1) was charged from the hopper side plate. The mixture was melt-kneaded under conditions of a temperature setting of 220°C and a rotor rotation speed of 80 rpm, and the kneaded product that maintained the molten state was sent to the single-screw extruder and granulated using a die (pelletizing head) with circular holes, a cooling water tank, and a pelletizer, to obtain pellets consisting of the resin composition (X-1). The resulting pellets of resin composition (X-1) were uniformly mixed and dispersed, and had a pellet diameter of 2.5 to 3.0 mm.
[0121] [Preparation of molded body] As a molded article made of the resin composition (X-1), a square plate having a length of 120 mm, a width of 130 mm, and a thickness of 1.0 mm was produced from the pellets obtained by the above-mentioned method using an injection molding machine (ES75SX III manufactured by Toshiba Machine Co., Ltd.; clamping force 735 kN, screw diameter Φ32 mm). The molding conditions were as follows. Cylinder temperature setting: 220~240℃ Screw speed: 100 rpm Injection pressure: 30~40MPa ·Injection speed: 25~30mm / sec Mold temperature: 40℃ ·Cooling time: 40 seconds
[0122] [Evaluation of physical properties of molded products] The physical properties of the molded bodies were evaluated using the following methods and are shown in Table 2. <Measurement of dynamic viscoelasticity> Test pieces were prepared by punching out the 1.0 mm thick square plates obtained by the method described above into dimensions of 35 mm length x 10 mm width, and using a rheometer (Anton Paar MCR301) to measure the temperature dispersion of the dynamic viscoelasticity from -60 to 150°C under conditions of torsion mode, frequency of 10 rad / s (1.6 Hz), strain setting of 0.1%, and heating rate of 2°C / min, the tan δ peak temperature and tan δ peak value were observed.
[0123] <Density of molded body> The square plate with a thickness of 1.0 mm obtained by the above-mentioned method was punched out to a size of 62 mm in length and 13 mm in width to prepare a test piece, and the density of the green body (g / cm3) was measured by the underwater displacement method according to JIS K7112. 3 ) was measured.
[0124] <Surface hardness> Six of the 1.0 mm thick square plates obtained by the above-mentioned method were stacked to form test pieces, and the Shore A hardness or Shore D hardness was measured immediately after and 15 seconds after the indenter of a hardness meter was pressed against the surface of the test piece at 23°C in accordance with ASTM D2240. Based on the obtained Shore A hardness or Shore D hardness, the value of ΔHS or ΔHS' was calculated according to the following formula. ΔHS = (Shore A hardness value immediately after the indenter starts contacting the surface - Shore A hardness value 15 seconds after the indenter starts contacting the surface) ΔHS' = (Shore D hardness value immediately after the indenter starts contacting the specimen - Shore D hardness value 15 seconds after the indenter starts contacting the specimen)
[0125] <Wrist fit test> A rectangular test piece was prepared by punching out a 3.0 mm thick square plate obtained in the same manner as above into a size of 125 mm long x 10 mm wide. The test piece was held between both hands for 30 seconds to soften it with body heat, and then the test piece was bent to fit the wrist. The load on the wrist at this time was evaluated by sensory evaluation. The meanings of the symbols in Table 2 are as follows. 〇: Can be bent with almost no strain on the wrist ×: Stress is felt on the wrist and bending along the wrist is not possible
[0126] <Nose compatibility test> A rectangular test piece was prepared by punching out a 3.0 mm thick square plate obtained in the same manner as above into a size of 125 mm long x 10 mm wide. The test piece was held between both hands for 30 seconds to soften it with body heat, and then the test piece was bent to fit the tip of the nose. The load on the nose at this time was evaluated by sensory evaluation. The meanings of the symbols in Table 2 are as follows. 〇: Can be bent with almost no stress on the nose ×: Pressure is felt on the nose, and bending along the tip of the nose is not possible
[0127] <Mold releasability> The mold releasability during injection molding was evaluated as follows. The symbols in Table 2 have the following meanings: 〇: Mold release possible without applying release agent ×: Difficult to release from the mold without applying release agent
[0128] [Examples 2 to 3] Resin compositions (X-2) and (X-3), molded bodies, and various test pieces were prepared and their physical properties were evaluated in the same manner as in Example 1, except that the amounts of 4-methyl-1-pentene / α-olefin copolymer (A-1), inorganic filler (B-1), and polystyrene-based thermoplastic elastomer (C2-1) were changed as shown in Table 2. The results are shown in Table 2.
[0129] Example 4 Except for changing 5 parts by mass of the polystyrene-based thermoplastic elastomer (C2-1) to 5 parts by mass of the polyolefin-based thermoplastic elastomer (C1-1), a resin composition (X-4), a molded body, and various test pieces were prepared and their physical properties were evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0130] Comparative Example 1 Resin compositions, molded articles, and various test pieces were prepared and their physical properties were evaluated in the same manner as in Example 1, except that the inorganic filler (B-1), the polyolefin-based thermoplastic elastomer (C1-1), and the polystyrene-based thermoplastic elastomer (C2-1) were not used, and 4-methyl-1-pentene·α-olefin copolymer (A-1) was used alone. The results are shown in Table 2.
[0131] Comparative Example 2 A resin composition containing 30 parts by mass of the propylene-based resin (D-1) and 70 parts by mass of the inorganic filler (B-1) was melt-kneaded in the same manner as described above to obtain pellets. The pellets were then used to prepare molded bodies and various test pieces in the manner described above, and the physical properties were evaluated as described above. The results are shown in Table 2.
[0132] Comparative Example 3 A resin composition containing 24 parts by mass of a propylene-based resin (D-1), 56 parts by mass of an inorganic filler (B-1), and 20 parts by mass of a polystyrene-based thermoplastic elastomer (C2-1) was melt-kneaded in the manner described above to obtain pellets. The pellets were then used to prepare molded bodies and various test pieces in the manner described above, and the physical properties were evaluated as described above. The results are shown in Table 2.
[0133] [Table 2]
[0134] As shown in Table 2, the molded articles made of the resin compositions (X-1) to (X-4) of Examples 1 to 4 have a tan δ peak temperature of 0°C to 60°C and a tan δ peak value of 0.6 to 5.0, as measured by dynamic viscoelasticity measurement (temperature range of -60 to 150°C) at a frequency of 10 rad / s (1.6 Hz), and therefore have excellent stress relaxation properties in the room temperature range and slowly recover to their original shape after elastic deformation. 3 More than 5.0g / cm 3 The results are shown in Table 1. In addition, since ΔHS is large, the molded product has a soft feel and is also soft to the touch. [Industrial Applicability]
[0135] The resin composition (X) and molded article of the present invention can be suitably used as daily necessities, toys, ear inserts, eyeglasses, wristwatches, and stationery. Daily necessities made of the resin composition (X) of the present invention include, for example, containers for food, tableware such as forks, spoons, and plates, containers with lids, and cosmetic compacts. Toys include, for example, models such as plastic models. Ear inserts include, for example, hearing aid components and earphone components.
Claims
1. 15 to 50 parts by mass of a 4-methyl-1-pentene / α-olefin copolymer (A); 10 to 80 parts by mass of an inorganic filler (B); Thermoplastic elastomer (C) 5 to 50 parts by mass (wherein the total amount of the 4-methyl-1-pentene / α-olefin copolymer (A), the inorganic filler (B), and the thermoplastic elastomer (C) is 100 parts by mass), A resin composition comprising: The resin composition satisfies the following requirements (X-a) to (X-c), The 4-methyl-1-pentene / α-olefin copolymer (A) satisfies the following requirements (A-a) to (A-b), the thermoplastic elastomer (C) is at least one selected from the group consisting of a polyolefin-based thermoplastic elastomer (C1) and a polystyrene-based thermoplastic elastomer (C2); The polyolefin-based thermoplastic elastomer (C1) satisfies the following requirement (C1-a): Resin composition (X); (X-a) the tan δ peak temperature, which is the temperature at which the loss tangent tan δ value determined by dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) becomes maximum in the temperature range of -60 to 150°C, is 0°C or higher and 60°C or lower; (X-b) the peak value of tan δ, which is the maximum value of loss tangent tan δ determined by dynamic viscoelasticity measurement at a frequency of 10 rad / s (1.6 Hz) in the temperature range of −60 to 150° C., is 0.6 or more and 5.0 or less; (X-c) density is 1.0 g / cm 3 5.0g / cm or more 3 Below is the result: (A-a) The 4-methyl-1-pentene / α-olefin copolymer (A) contains 55 to 90 mol % of structural units derived from 4-methyl-1-pentene and 10 to 45 mol % of structural units derived from an α-olefin having 2 to 4 carbon atoms (wherein the total of the structural units derived from 4-methyl-1-pentene and the structural units derived from an α-olefin having 2 to 4 carbon atoms is 100 mol %); (A-b) the tan δ peak temperature is 15° C. or higher and 45° C. or lower; (C1-a) The tan δ peak temperature is less than 15°C.
2. The resin composition (X) according to claim 1, comprising more than 50 parts by mass and not more than 80 parts by mass of the inorganic filler (B).
3. The resin composition (X) according to claim 1, wherein the 4-methyl-1-pentene / α-olefin copolymer (A) satisfies the following requirements (Ac) to (Ad): (A-c) the tan δ peak value is 0.6 or more and 5.0 or less; (Ad) The melting point measured by a differential scanning calorimeter (DSC) is 160° C. or lower, or no melting point is observed by a differential scanning calorimeter (DSC).
4. The resin composition (X) according to claim 1, wherein the inorganic filler (B) is at least one selected from the group consisting of calcium carbonate, magnesium sulfate, barium sulfate, magnesium oxide and talc.
5. The resin composition (X) according to claim 1, wherein the inorganic filler (B) has an average particle size of 0.01 to 100 μm.
6. A molded article made of the resin composition (X) according to any one of claims 1 to 5.
7. A wearable member comprising the resin composition (X) according to any one of claims 1 to 5.
8. A toy comprising the resin composition (X) according to any one of claims 1 to 5.
9. An ear insert member comprising the resin composition (X) according to any one of claims 1 to 5.
10. A wristwatch component made of the resin composition (X) according to any one of claims 1 to 5.
11. A spectacle member comprising the resin composition (X) according to any one of claims 1 to 5.
12. A stationery item comprising the resin composition (X) according to any one of claims 1 to 5.
13. A tableware made of the resin composition (X) according to any one of claims 1 to 5.
Citation Information
Patent Citations
Production of ecological paper and composition therefor
JP2001071378A
Additive for polyolefin resin sheet and resin composition for the sheet compounded with the same
JP2003026866A
Method for producing pellets, production method for resin molding, and pellets
WO2018092494A1